The Effect of Cognitive Behavioral Counseling with Role-Playing Techniques to Increase Self-Confidence of Class VIII Students at SMP Negeri 1 Seririt - Anastasya Dilla Tebina Br Pelawi; Nyoman Dantes (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Self-confidence in adolescents plays a very important role in their developmental stage. When adolescents feel confident, they tend to be better able to face various challenges and social situations. It is not only about how adolescents deal with challenges or achieve goals, but also about forming a strong and positive personality foundation during adolescence. This study aims to determine and describe the effect of cognitive behavioural counselling using the role-playing technique to increase the self-confidence of eight Grade students (Sekolah Penggerak) with a sample of 5 students. This research is an experimental study using a one-group pre-test post-test design. The study population comprised all eight Grade students (Sekolah Penggerak). The data analysis method used in this study is a non-parametric test applying the Wilcoxon test. The results of this study show that cognitive behavioural counselling with the role-playing technique is effective or has an influence in increasing the self-confidence of eight Grade students, with a result of p < α = 0.042 < 0.05. Thus, it can be concluded that there is a significant effect of cognitive behavioural counselling using the role-playing technique on increasing students’ self-confidence. This study is also expected to serve as a reference for future researchers to apply a similar approach with different techniques or to explore other psychological variables.